(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The classification of euphemisms and how they came to be used in Uzbek and English are covered in this article. We will attempt to demonstrate this claim in this article while also outlining some of the motivations behind the euphemistic inventions. This may include a variety of linguistic and extralinguistic factors that contribute to the creation of new lexical items like euphemisms. Most of the time, euphemisms serve as more than just a stylistic synonym or a substitute for any language element. They change the emotional predominance, provide a fresh examination of a particular phenomenon, a fresh angle on its consideration, and offer a fresh moral and ethical evaluation of the phenomenon.